Accuracy of Cone-Beam Computed Tomography in Measuring the Thickness of Radicular Dentin - Bunn,Daiana Lopes (2020)
Abstract The purpose of this study was to evaluate the accuracy of Cone-Beam Computed Tomography (CBCT) in measuring radicular dentin thickness focused on intraradicular post placement planning treatment. Ten single-rooted human premolars were selected. The teeth were divided into three segments (cervical, middle and apical). The coronal face of the apical and middle sections was selected for the dentin thickness assessment; which was measured from the external root surface to the root canal wall, on the buccal, lingual, mesial, and distal surfaces of each tooth. In situ anatomical measurement was the reference standard, and the corresponding axial CBCT imaging were evaluated by the i-CAT software. The one-way ANOVA test and the Bonferroni post hoc test were applied to compare the groups (p>0.05). CBCT imaging measurements (p=0.003) overestimated the radicular dentin thickness compared to the reference standard. Descriptive analysis showed that the greatest difference between the reference standard and the tomographic measurement means were 0.20 mm. One-way ANOVA test found the statistical significant difference among group’s measurements. Bonferroni correction demonstrated statistically significant difference only related lingual surface for the CBCT imaging measurements. CBCT imaging measurements overestimated the radicular dentin thickness. However, the measurement difference was clinically acceptable.